Perjalanan Sejarah Perkembangan Kendo dari Abad Pertengahan hingga Zaman Modern - Zainab Ali Abdul Ameer (Indonesian Journal of Physical Education and Sport Science, 2025)
Study Purpose. highlighting the origins of the sport's philosophy. Studying the development of the sport of kendo across different historical periods and its adaptation to societal and cultural changes. Identifying the establishment of the most prominent organizations and federations that contributed to its development, and exploring the sport's basic tools and rules and its most prominent championships. Materials and Methods. The historical approach was adopted in studying the historical process of the development of kendo, as it is appropriate to the nature of the problem. The information has been simplified and presented in a sequential manner that presents the development of the sport of kendo, starting from the origins of its philosophy, its origins, and the development of its equipment and basic rules, in light of the cultural and social changes from the Middle Ages to the modern era, relying on several historical, cultural, and sporting scientific references related to the sport of kendo, including books and research articles, Official documents and data are available on the official websites of the International Kendo Federation. Results. The integration of women into this sport progressed slowly, as kendo was traditionally viewed as a male-only activity for many years. This perception may be attributed to the cultural traditions of Japanese society, which played a significant role in the development of kendo and its status as a martial art rooted in historical battles. Conclusions. The sport of kendo has been shaped by various traditional philosophies, concepts, and principles that represent the culture of Japanese society. These influences include samurai traditions, Zen Buddhism, the values of bushido, and the principles of kenjutsu. As a result, kendo has evolved from a mere martial art into a philosophical system that encompasses physical, mental, and spiritual development.